Epilepsy in Norrie disease - V. A. Aysina; О. V. Kozhevnikova; О. V. Osipova; A. V. Lashkova (Эпилепсия и пароксизмальные состояния, 2022)
The insight into the Norrie disease viewed from neurology perspective and clinical case of refractory epilepsy relevant to the disease are considered. Epilepsy rarely accompanies Norrie disease. The dynamics of changes  in electroencephalograms (EEG) and types of epileptic seizures during the disease progression as well as depending on the therapy received in the clinical case is analyzed. It is relevant for patients with Norrie disease to regularly undergo video-EEG monitoring to detect epileptiform activity, ictal patterns for timely diagnostics of epilepsy followed by prescribing  proper therapy to improve quality of life.